(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hakim L, Widyorini R, Nugroho WD, Prayitno TA. 2021. Radial variability of fibrovascular bundle properties of salacca (Salacca zalacca) fronds cultivated on Turi Agrotourism in Yogyakarta, Indonesia. Biodiversitas 22: 3594-3603. Fibrovascular bundles have properties variability not only based on species and varieties but also parts of species. This study, therefore, aims to characterize the FVB fundamental properties (anatomical, chemical, physical and mechanical) of Salacca zalacca (Gaertn.) Voss fronds, based on radial direction. The salacca fronds were divided into three parts, outer, middle as well as inner positions. Then the FVB’s anatomical and physical properties were observed by light microscope and gravimetry analysis, respectively. Meanwhile, the variability of chemical and mechanical properties was investigated based on the ASTM standard. According to the results, the outer position has a higher variability of diameter, density, cellulose, lignin, and mechanical properties than the inner position, but has a lower hemicellulose value than the middle and inner position. Furthermore, the relationships between the anatomical, physical, chemical, and mechanical properties were discovered to form a pattern where increasing the mechanical properties is influenced by density and ratio vascular tissue area to total transverse area. Based on the results, the fibrovascular bundle of S. zalacca frond was concluded to possess anatomical, physical, chemical, and mechanical properties variability on the radial direction. There was a correlation between anatomical properties and mechanical properties.